Gambaran Efek Samping Pada Akseptor Kontrasepsi Hormonal Di Puskesmas Colomadu 2 Kabupaten Karanganyar - Perkasa, Tomy (2016)
OVERVIEW OF SIDE EFFECTS OF HORMONAL CONTRACEPTION IN HEALTH COLOMADU 2 KARANGANYAR By: Tomy Perkasa ABSTRACT Background :Family planning acceptors using hormonal contraception within a certain time often complain of health problems, one of the health problems that are often experienced by the acceptor CICs is hypertension, or high-pressure virgin. Purpose :The purpose of this study is to analyze the picture of the side effects of hormonal contraceptives in health centers Colomadu 2 Karanganyar. The results are expected are expected to contribute concepts and theories related to side effects of hormonal contraceptive use. Method :This research uses descriptive quantitative method. Population and sample in this study are all women who have married and the use of hormonal contraceptives and recorded in Puskesmas Colomadu 2 Karanganyar totaling 119 people composed of 38 people using contraceptive injections, 42 people use contraception implat, 32 people use pills and 7 people Hormonal IUD contraceptive use. The sampling technique used is total sampling. Analysis of the data used in this study were univariate analyzes each variable that research to produce a frequency distribution and percentage of each variable. Result :The results showed that the injectable contraceptive users recorded in Puskesmas Colomadu 2 Karanganyar experience side effects on menstrual disorders (amenorrhea). Implant contraceptive users recorded in Puskesmas Colomadu 2 Karanganyar experience side effects amenorrhea. Users pills recorded in Puskesmas Colomadu 2 Karanganyar experience side effects of weight gain. Hormonal contraceptive IUD users recorded in Puskesmas Colomadu 2 Karanganyar experience side effects of pain / pain. Keywords: contraception, hormonal side effects